Rancang Bangun Sistem Pengaman Rumah Berbasis Internet IoT - Moch Hatta; Khoiril Anam; Achmad Fredi Maharsyah; Alief Yudha Karna (KERNEL: Jurnal Riset Inovasi Bidang Informatika dan Pendidikan Informatika, 2025)
Smart homes have experienced rapid development with the adoption of Internet of Things (IoT) technology. The use of IoT in the context of home security provides the ability to control, monitor, and secure the home environment more efficiently and effectively. However, the increasing connection of these devices also brings significant security risks, such as threats to personal data, privacy, and system integrity. This study explores the latest approaches and technologies in securing IoT-based homes. The main focus is on identifying and mitigating security risks that arise from the connectivity of devices such as CCTV cameras, door sensors, alarm systems, and other control devices. The research method involves analyzing the communication protocols used, access rights management, and the implementation of encryption and other security techniques. The overall system success percentage is 85%, which shows quite good performance. However, to improve the quality of the system, further attention is needed to the stability of the internet network used by NodeMCU. In conclusion, the integration of IoT in smart homes promises convenience and comfort, but must be accompanied by serious efforts to ensure user security and privacy are maintained.